Situating person memory: the role of the visual context on memory for behavioral information - Palma, T. A. (2014)
Person memory has been mainly investigated as an individual process. In contrast, we argue that person memory results from the interplay between the individual and the context. Thus, the way people acquire and retrieve social information is constrained by the context in which these processes take place. This argument was explored in three experiments. In an impression formation paradigm, we manipulated the meaningfulness of contextual information (objects) for a stereotypical target. Results showed that meaningful contextual information presented during the encoding of behavioral information improved memory.for the behavioral information but also for the contextual information (Experiment 1-2); that this memory advantage only occurs when the encoding goal requires some degree of cognitive organization (Experiment 2); and finally, that meaningful contextual information also enhances memory when presented at retrieval (Experiment 3). These results are consistent with a situated cognition perspective according to which the context where cognitive activities take place can be used to facilitate cognitive activity. We discuss the implications of these results for the standard person memory view and identify new routes for future research.